Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Air Mineral Merek Aqua Pada Shekar Brillyan Renata (SBR) Mart Di Desa Janju Kecamatan Tanah Grogot - M. Yunus Syam; Tegen Sayuk Rimboko; Tri Putri Yulianita (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The purpose of this research is to determine the influence of Brand Image and Product Quality on the Decision to Purchase Aqua Brand Mineral Water at Shekar Brillyan Renata (SBR) MART in Janju Village, Tanah Grogot District, jointly (simultaneously) or individually (partially) and which variables which is more dominant. The respondents in this research were an unlimited number of consumers (no purchase records) who were taken by chance when the questionnaire was distributed. The validity test results of the 18 statements in this study were declared valid because rcount > rtable (0.3160). Then, the reliability test results in this study were 0.907, so all statements were reliable because Cronbach's Alpha was 0.907 > 0.6. Based on the multiple linear regression equation Y = 72.572 + 0.344 X1 + 0.498 X2. The multiple correlation coefficient (R) value of 0.864 is at a relationship level of 0.80-1.000, which means the correlation is at a very strong level between the independent variables consisting of variables from Brand Image (X1), Product Quality (X2), to the dependent variable, namely Purchase Decision (Y) at Shekar Brillyan Renata (SBR) MART in Janju Village, Tanah Grogot District. The value of the R-Square results is 0.746, meaning that 74.6% of the dependent variable, namely purchasing decisions (Y), is influenced by independent variables consisting of brand image (X1) and product quality (X2), while the remaining 25.4% is influenced by other factors not examined in this study. F test results (simultaneous) value Fcount > Ftable (39.647 > 3.35) and significant level (0.000 < 0.05). So that the variables brand image (X1) and product quality (X2) have a significant effect on purchasing decisions (Y) at Shekar Brillyan Renata (SBR) MART in Janju Village, Tanah Grogot District. The results of the t test (partial) tcount value for the brand image variable (X1) is 2.934. The tcount value for the product quality variable (X2) is 3.687, both tcount values ​​> ttable (1.703) so brand image (X1) and product quality (X2) have significant influence on Purchasing Decisions (Y). It can be concluded from the results of the t test that the product quality variable (X2) has a dominant influence on Purchasing Decisions (Y) at Shekar Brillyan Renata (SBR) MART in Janju Village, Tanah Grogot District.